2013
DOI: 10.2527/jas.2012-5669
|View full text |Cite
|
Sign up to set email alerts
|

Short-term feed restriction impairs the absorptive function of the reticulo-rumen and total tract barrier function in beef cattle1

Abstract: The objective of this study was to evaluate whether different severities of short-term feed restriction (FR) affect the absorptive function of the reticulo-rumen and total tract barrier function in beef cattle. Eighteen ruminally cannulated and ovariectomized Angus × Hereford heifers were blocked by BW into 3 blocks, with blocks conducted sequentially. Treatments were imposed during the 5-d FR period by restricting heifers to 75 (FR75), 50 (FR50) or 25% (FR25) of the ad libitum feed intake measured during a 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
95
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(105 citation statements)
references
References 67 publications
(87 reference statements)
8
95
1
1
Order By: Relevance
“…Calves were kept in crates for 48 h to facilitate measurement of total urine excretion over 2 consecutive 24-h periods. Zhang et al (2013) validated the use of Cr-EDTA as an in vivo barrier function measurement and reported that 99% of the Cr excreted in urine was recovered within 48 h from the time of dosing. An initial validation was conducted for this study (data not shown) and results corroborated with Zhang et al (2013).…”
Section: In Vivo Total-tract Permeabilitymentioning
confidence: 98%
See 4 more Smart Citations
“…Calves were kept in crates for 48 h to facilitate measurement of total urine excretion over 2 consecutive 24-h periods. Zhang et al (2013) validated the use of Cr-EDTA as an in vivo barrier function measurement and reported that 99% of the Cr excreted in urine was recovered within 48 h from the time of dosing. An initial validation was conducted for this study (data not shown) and results corroborated with Zhang et al (2013).…”
Section: In Vivo Total-tract Permeabilitymentioning
confidence: 98%
“…Zhang et al (2013) validated the use of Cr-EDTA as an in vivo barrier function measurement and reported that 99% of the Cr excreted in urine was recovered within 48 h from the time of dosing. An initial validation was conducted for this study (data not shown) and results corroborated with Zhang et al (2013). Each day, total urine weight was measured and a 40-mL sample was obtained and frozen at −20°C until being analyzed for Cr concentration as described by Vicente et al (2004) using atomic absorption (iCE 3000 series, Thermo Fisher Scientific Inc., Waltham, MA).…”
Section: In Vivo Total-tract Permeabilitymentioning
confidence: 98%
See 3 more Smart Citations